2022
DOI: 10.3389/fendo.2022.893848
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation Improves Mitochondrial Function and Reduces Inflammation in Placentae of Obese Women

Abstract: BackgroundAbout 30% of women entering pregnancy in the US are obese. We have previously reported mitochondrial dysregulation and increased inflammation in the placentae of obese women. Vitamin D (VitD) is a major player in calcium uptake and was shown to modulate mitochondrial respiration and the immune/inflammation system. Studies show decreased VitD levels in obese individuals; however, the effect of maternal obesity on VitD metabolism and its association with placental function remains understudied.MethodsM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…This runaway reprogramming of glucose metabolism can be restored by paricalcitol, a VDR agonist. VDR can inhibit glycolysis in colorectal cancer (Zuo et al, 2020), and VD supplementation can improve mitochondrial respiration in primary trophoblasts isolated from obese women (Phillips et al, 2022) In our animal experiments, we confirmed the regulatory effect of VDR on p-PDHA1; however, the specific regulatory mechanism is still unclear. PDHA1 is a key site regulating PDHc, and its phosphorylation is involved in the pathological mechanism of many diseases.…”
Section: Frontiers In Physiologysupporting
confidence: 71%
“…This runaway reprogramming of glucose metabolism can be restored by paricalcitol, a VDR agonist. VDR can inhibit glycolysis in colorectal cancer (Zuo et al, 2020), and VD supplementation can improve mitochondrial respiration in primary trophoblasts isolated from obese women (Phillips et al, 2022) In our animal experiments, we confirmed the regulatory effect of VDR on p-PDHA1; however, the specific regulatory mechanism is still unclear. PDHA1 is a key site regulating PDHc, and its phosphorylation is involved in the pathological mechanism of many diseases.…”
Section: Frontiers In Physiologysupporting
confidence: 71%
“…This study, done in Oregon in the United States (45° N), showed that vitamin D deficiency is, at least partially, responsible for mitochondrial dysfunction and increased placental inflammation among women with obesity. Therefore, receiving adequate amounts of vitamin D is very important to maintain normal placental function 34 in the context of maternal obesity 35 . Based on findings from a clinical trial of vitamin D supplementation during pregnancy, the authors suggested increased supplementation doses of vitamin D for pregnant women who had vitamin D insufficiency in early pregnancy, higher pregnancy weight gain, or an expected birth during the winter 32 …”
Section: Resultsmentioning
confidence: 99%
“…Obesity and low vitamin D concentrations among pregnant women are associated with newborns having low vitamin D concentrations at birth 33 . A recent study showed that low vitamin D levels in umbilical cord blood among women with obesity were correlated with a decreased ratio between fetal and placental weights, an indicator of placental insufficiency 35 . This suggests that placental transfer of vitamin D is impaired in women with obesity, explaining the lower levels of vitamin D in their newborns.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, vitamin D has been shown to prevent osteoporosis in the elderly, while it increases resistance to COVID-19 in appropriate concentrations ( 35 ). In women and children, vitamin D deficiency can lead to placental dysgenesis, affecting the innate development and immunity of infants and children ( 32 , 35 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vitamin D can change the composition of the intestinal flora through regulation of the expression of antibacterial peptides, in addition to immune regulation ( 31 ). Phillips et al ( 32 ) demonstrated that vitamin D may provide some protection against increased mitochondrial dysfunction and inflammation in the placenta of obese women. In addition, Hahn et al ( 33 ) indicated that long-term vitamin D supplementation may be effective for reducing the incidence of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%